The Aftermath of Hobby Lobby and Obergefell: A Reconceptualization of Religious Freedom in the United States and its Potential Implications for Public Schools and Pluralist Democracies. Issue 2 (4th March 2017) - Bindewald, Benjamin J.; Rosenblith, Suzanne; Green, Bob
Abstract : Restricting public employees' free exercise rights or the State to maintain neutrality toward religion has been longstanding precedent in the United States. It has certainly been the case in US public schools beginning in the 1940s and affirmed through the courts over and again through much of the 20th century. The aftermath of 2 recent Supreme Court decisions challenges this long-held precedent, however, as it has led to several instances in which public employees have requested religious exemptions from their professional obligations (e.g., Kentucky court clerk Kim Davis' refusal to grant marriage certificates to same-sex couples). This article provides a foundational framework for exploring the recent reconceptualization of religious freedom and its possible implications for public schools and the larger project of advancing a liberal, pluralist democracy were teachers to refuse to fulfill central elements of their job on the basis of religious objections.